PENDAMPINGAN BUDIDAYA JAMUR TIRAM SEBAGAI SARANA PEMBERDAYAAN EKONOMI UMAT DI KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO - Ummal Khoiriyah; Risma Fahrul Amin (As-Sidanah, 2020)
The mosque is an instrument of empowering the people that has a very strategic role in efforts to improve the quality of society. Mosques are used as a center of activity in Islamic socitey. Since the time of the Prophet, the mosque has been a center for empowering the people that has had an unlimited role. This outreach program aims to assist the mosque management in Banyuputih District, Situbondo Regency in planning and designing programs to strengthen the function of mosques in the economic empowerment of the people. From the results of this outreach program, it can be concluded that the efforts that had been made by mosque management in running a Mosque-Based Society Service Center was running a mushroom cultivation business which includes the production process, quality control, and marketing.